DIGITAL BANKING ADOPTION, BANK SIZE, AND BANK PERFORMANCE IN INDONESIA - Rahmat Setiawan; Leonardus Prakoso (Jurnal Ekonomi dan Bisnis Airlangga)
Introduction: The adoption of technology has become prevalent in the banking sector. This research investigates the potential correlation between the implementation of digital banking adoption and the bank performance (Return on Assets and Operational Efficiency Rasio), while considering the factor of bank size.